Feedback Facilitated Relaxation Training in School Counseling - Volpe, Richard (Canadian Journal of Counselling and Psychotherapy, 2012)
In a broad sense, tension involves anxiety and insecurity while relaxation refers to self-comfort and confidence. Research has indicated that tension can facilitate or inhibit learning. Although optimal levels are poorly understood, there appears to be an inverse relationship between relaxation and debilitating tension. Biofeedback training has made it possible to investigate the process of physiological arousal andvoluntary control more clearly.The knowledge of tension unlearning and relaxation teaching can be used by the counselor in his work with both average and hyperkinetic studentsin the areas of attention and concentration, for example. Training in such skills can be lifelong assets in coping with interpersonal and educational situations in daily life.